Marketing Politik di Media dan Softening News Gibran Rakabuming Raka dalam Pemilihan Wali Kota Solo - Jeani Riyanti (Universitas Ahmad Dahlan, 2020)
The fourth Simultaneous Regional Election, or Pilkada, will be held in December 2020. However, the future-elected-candidate in simultaneous Regional Election will only have a shorter period of time, but many candidates with various backgrounds might enrol during this election. One of the candidates might be Gibran Rakabuming Raka, who will join election as Mayor in Solo. Gibran is the eldest son of Presiden Indonesia, Joko Widodo. We could find pros and cons during his contestation. Gibran had been enrolled as a member of Partai Demokrasi Indonesia Perjuangan (PDIP) as his political vehicle to win the election. PDIP itself is open for any possibilities that want to be regional leaders from PDIP. PDIP had not been decided yet on the candidate who will compete for regional election. Nevertheless, Gibran has been preparing his strategies to be a candidate from PDIP for the Regional Election in Solo. A candidate or political party applied political marketing to achieve him/her/their goal, which is winning the election. Related to the oriented party concept from Lees-Marshment, Gibran tried to apply value from PDIP. His public appearance in the media and activity of blusukan are carried out so will be in line with the value of PDIP. Besides news coverage of pro-cons of the election, there are many softening news about Gibran instead of his working program for the election.